Educational Landscape in Media Space: Methodology of Mapping and Description - M. N. Kicherova; M. Yu. Semenov; I. S. Trifonova (Научный диалог, 2024)
This article focuses on the emergence of new aggregator platforms within media space that showcase a variety of educational courses and programs at different levels. The aim of the study is to identify the specifics of the methodology for mapping the educational landscape in media space at global, national, and local levels, particularly in the context of exploring adult education ecosystems. The theoretical framework is grounded in an ecosystemic approach to education, employing qualitative content analysis, comparison, and juxtaposition as research methods. The analysis of the mapping methodology is based on metrics delineated by the authors, drawn from scholarly sources and analytical reports that elucidate the characteristics of the contemporary educational landscape and its representation in media space. The educational landscape is examined as a complex sociocultural phenomenon. General and specific principles of its media mapping are identified, taking into account various scales, with a common principle being the combination of both bottom-up and top-down strategies for data collection and analysis. The modern educational landscape is described with consideration of the diversity of ecosystemic connections. The authors demonstrate the potential of this methodology and emphasize that media mapping of the educational landscape allows for the identification of key providers, the establishment of pathways for adult learning, and the synchronization of supply and demand for skills in the labor market.